Thermomechanical Characterization Of Particleboards From Powder Typha Leaves - Younouss Di̇eye (Journal of Sustainable Construction Materials and Technologies, 2019)
New composite boards with low-thermal conductivity produced from a mixture of powder Typha leaves and a binder as gum arabic have been developed. The goal of this paper was to investigate the effect of binder content on compressive strength and thermal properties of typha panels. The results showed that the panels with a binder content of 33.33–50 % had the thermal conductivity values ranging from 0.055 to 0.083 W.m-1.K-1, which was close to that of many natural insulating materials. The compressive strength values obtained were comparable to those of the lime – hemp concrete. This study showed that typha possesses interesting capacities of insulating and its combination with gum arabic contributes to the improvement of thermal comfort, to the reduction of the energy consumption as well as to the emissions of CO2.